Unsteady Boundary Layer Flow And Heat Transfer In Nanofluids With Microorganisms - Basir, Mohammad Faisal Mohd (2018)
Boundary layer flows involving microorganism have attracted attention in recent years. Several problems involving such flows are investigated in detail in this thesis. The problems involve two dimensional laminar convective and threedimensional boundary layer flow with heat, mass and microorganism transfer under various physical configurations in the presence of velocity slip, thermal slip, mass slip, microorganism slip, Stefan blowing and zero mass flux boundary conditions. The fluid is assumed to be Newtonian (water), viscous, incompressible and has constant or variable transport properties.